Śrī Rāya Rāmānanda Saṁvāda: the conversation between Śrī Caitanya Mahāprabhu & Śrī Rāmānanda Rāya - Kṛṣṇadāsa Kavirāja Gosvāmī (Gaudiya Vedanta Publications, 2025)
Śrīśrīcaitanyacaritāmṛta <English & Bengali> / Chapter VIII